In silico Identification of the HLA-DRB1*15:01 Restricted B-cell and T-cell Epitopes of the Autoantigens MOG and AQP4 Associated with Autoimmune Neuropathy - Nhan, Le Thi Thanh; Van, Ha Thao; Thao, Bui Phuong; Phuong, Le Lan; Thai, Trinh Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5798, 2026)
Immunogenicity plays a crucial role in the pathogenesis of autoimmune neuropathy associated with MOG and AQP4 proteins. Hence, we employed computational tools, including MHC-II Binding Prediction and B Cell Epitope Prediction tools from IEDB, Clustal Omega, SWISS-MODEL, AbodyBuilder, HDOCK, AlphaFold Protein Structure Database, and Protein Data Bank, to identify potential HLA-DRB1*15:01 restricted T-cell and B-cell epitopes of the autoantigens MOG and AQP4 and their structural characteristics. Subsequently, the peptide sequences of bacterial proteins identical to the epitopes of MOG and AQP4 proteins were analyzed using BLASTp, MoRFchibi SYSTEM, IUPred3, SEG, miPepBase, and NCBI databases to detect the presence of MoRF, SliM, and LCR. Our findings revealed that MOG 22-LQVSSSY-28 , MOG 80-YRNGKD-85 , MOG 179-QYRLRGKL-186 and AQP4 75-CTRKIS-80 were common sequences of the HLA-DRB1*15:01 restricted T-cell and B-cell epitopes of the autoantigens MOG and AQP4. While MoRFs and LCRs were found in some bacteria, the prevalence was low (10.81% and 5.40%, respectively). This suggests that these bacteria may not use the identical peptides to regulate protein-protein interactions and host cell activities.